Application of quantum dots in perovskite solar cells. (8th September 2021) - Zheng, Fei; Liu, Yifan; Ren, Weihua; Sunli, Zetong; Xie, Xiangyu; Cui, Yanxia; Hao, Yuying
Abstract: Perovskite solar cells (PSCs) are important candidates for next-generation thin-film photovoltaic technology due to their superior performance in energy harvesting. At present, their photoelectric conversion efficiencies (PCEs) are comparable to those of silicon-based solar cells. PSCs usually have a multi-layer structure. Therefore, they face the problem that the energy levels between adjacent layers often mismatch each other. Meanwhile, large numbers of defects are often introduced due to the solution preparation procedures. Furthermore, the perovskite is prone to degradation under ultraviolet (UV) irradiation. These problems could degrade the efficiency and stability of PSCs. In order to solve these problems, quantum dots (QDs), a kind of low-dimensional semiconductor material, have been recently introduced into PSCs as charge transport materials, interfacial modification materials, dopants and luminescent down-shifting materials. By these strategies, the energy alignment and interfacial conditions are improved, the defects are efficiently passivated, and the instability of perovskite under UV irradiation is suppressed. So the device efficiency and stability are both improved. In this paper, we overview the recent progress of QDs' utilizations in PSCs.